"Pit-dot" ultrathin nanosheets of hydrated copper pyrophosphate as efficient pre-catalysts for robust water oxidation. Issue 87 (18th October 2021) - Xie, Junfeng; Yang, Xueying; Wang, Yameng; Kang, Luyao; Li, Jiechen; Wei, Zimeng; Hao, Pin; Lei, Fengcai; Wang, Qian; Tang, Bo
Abstract : "Pit-dot" Cu2 P2 O7 ·3H2 O ultrathin nanosheets with boosted pre-oxidation behavior were fabricated as efficient pre-catalysts for highly efficient and durable oxygen evolution reactions. Abstract : Herein, hydrated copper pyrophosphate ultrathin nanosheets with a unique "pit-dot" nanostructure were fabricated as efficient pre-catalysts for the oxygen evolution reaction, and systematic post-catalytic characterization studies confirmed the important role of the boosted pre-oxidation reaction in promoting the OER catalysis.